Clinical effects of caraway, a traditional medicine for weight loss - Kazemipoor, M. (Elsevier, 2014)
The seeds of caraway (Carum carvi L.), a potent medicinal plant, are traditionally used for inducing weight loss. In this study, the anti-obesity properties of caraway aqueous extract (CAE) at 30 mL/day are examined in a randomized, triple-blind, placebo-controlled clinical study. At baseline, seventy overweight and obese, healthy, aerobic-trained, women were randomly assigned to two groups (n=35 per group). After 12 weeks, the CAE group, compared with placebo, showed a significant decrease in weight, body mass index, body fat percentage, and anthropometric indices. No changes were detected in the clinical and para-clinical assessments of participants. The findings show that dietary CAE with no limit in diet, when combined with physical activity, is of value in the treatment of obesity in women, lowering their weight, BMI, body fat percentage, and body size, and has no negative clinical effects. This trial is registered as NCT01833377.